Prevalência de lesões cervicais não cariosas relacionadas à má oclusão em discentes da Faculdade de Odontologia da Universidade Federal do Pará - RIBEIRO, Aldrian Oliveira (2023)
Non-carious cervical lesions (LCNC) are characterized by the loss of tooth structure without the participation of microorganisms. Although its origin mechanism is still not well understood, it is assumed that the incidence of horizontal forces from malocclusion can be considered as one of its etiologies. In view of this, the objective of the present study was to assess the prevalence of LCNC related to malocclusion in students of the Faculty of Dentistry of the Federal University of Pará (UFPA). Thirty-nine students were selected and evaluated, these undergoing anamnesis and clinical examination (with the aid of a periodontal probe, exploratory probe and dental mirror) to analyze the presence, location, shape and severity of the lesion, as well as any type of occlusal instability. Occlusal aspects were assessed to determine the presence or absence of characteristics that indicate an undesirable occlusion, such as the presence of eccentric occlusal contacts, evaluating protrusion and laterality through occlusal contact demarcation tape. The data obtained were tabulated in the Microsoft Excel program (Version PT / 2016) for frequency analysis.As a result, it was observed that 69.2% of the patients analyzed had LCNC, with a higher prevalence in males (53%), where dental contacts considered harmful (A + C and A, B, C alone) were more prevalent, in addition to of a greater presence of lesions with minimal loss of dental structure (50%) and with the lower first premolars as the most affected teeth (25%). It was concluded, then, that the occurrence of LCNC is associated with several factors and may be related to unfavorable occlusal contacts.